Reducing urinary tract infections in care homes by improving hydration - Charles Vincent; Katie Lean; Rasanat Fatima Nawaz; Sundus Jawad (BMJ Open Quality)
Dehydration may increase the risk of urinary tract infections (UTIs), which can lead to confusion, falls, acute kidney injury and hospital admission. We aimed to reduce the number of UTIs in care home residents which require admission to hospital. The principal intervention was the introduction of seven structured drink rounds every day accompanied by staff training and raising awareness. UTIs requiring antibiotics reduced by 58% and UTIs requiring hospital admissions reduced by 36%, when averaged across the four care homes. Care home residents benefited from greater fluid intake, which in turn may have reduced infection. Structured drink rounds were a low-cost intervention for preventing UTIs and implemented easily by care staff.